Energy and nitrogen balances in very low birthweight infants. Issue 8 (August 1987) - De Curtis, M; Brooke, O G
Abstract : Energy and nitrogen balances were performed in 12 very low birthweight infants fed on either human milk or on a preterm formula. Energy and nitrogen retention were significantly higher in those given the formula feed (p less than 0.05). Highly significant correlations were found between nitrogen intake and nitrogen retention and between energy retention and nitrogen retention (p less than 0.001). Multiple regression analysis failed to show any effect of energy retention on the correlation between nitrogen intake and nitrogen retention in babies fed on human milk. Protein deficiency seems to be the most likely explanation of poor growth in infants fed on human milk.